2016
DOI: 10.1128/jvi.00581-16
|View full text |Cite
|
Sign up to set email alerts
|

The Interferon-Stimulated GeneIfitm3Restricts West Nile Virus Infection and Pathogenesis

Abstract: T he interferon (IFN)-induced transmembrane protein (IFITM) genes consist of a family of genes encoding related proteins: Ifitm1,2,3,5,6,7, and 10 in mice and IFITM1, 2, 3, 5, and 10 in humans (1, 2). The expression of several IFITM genes (e.g., those encoding IFITM1, 2, and 3) can be induced by type I, II, or III IFNs (3, 4). Although initial studies described possible roles of IFITM1, IFITM2, and IFITM3 in development, apoptosis, cell proliferation, and cell signaling (5-13), a subsequent report suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 86 publications
2
71
0
Order By: Relevance
“…The reasons for this discrepancy are not clear at present but may relate to altered gene expression kinetics of these two transcripts during naturally-acquired infection. In addition, previous studies have shown that IFITM1 is expressed on the plasma membrane and the early endosomes while IFITM3 can be preferentially detected in late endosomes(Bailey et al, 2014; Gorman et al, 2016; Monel et al, 2017; Savidis et al, 2016b). Nevertheless, there is evidence that ZIKV can antagonize interferon-signaling pathways by targeting key proteins involved in signaling downstream of the IFN receptor.…”
Section: Discussionmentioning
confidence: 93%
“…The reasons for this discrepancy are not clear at present but may relate to altered gene expression kinetics of these two transcripts during naturally-acquired infection. In addition, previous studies have shown that IFITM1 is expressed on the plasma membrane and the early endosomes while IFITM3 can be preferentially detected in late endosomes(Bailey et al, 2014; Gorman et al, 2016; Monel et al, 2017; Savidis et al, 2016b). Nevertheless, there is evidence that ZIKV can antagonize interferon-signaling pathways by targeting key proteins involved in signaling downstream of the IFN receptor.…”
Section: Discussionmentioning
confidence: 93%
“…Among the ISGs, those encoding IFN-induced transmembrane (IFITM) proteins, including IFITM1, IFITM2, and IFITM3, are widely expressed and can be induced by all three types of IFNs in many cell types. The IFITMs localize at the cell plasma membrane and endocytic vesicles and restrict the entry of enveloped RNA viruses from nine viral families (5), including some medically important human pathogens, such as influenza A virus (IAV), dengue virus (DENV), West Nile virus, Zika virus, chikungunya virus, Ebola virus (EBOV), Rift Valley fever virus, human immunodeficiency virus (HIV), and hepatitis C virus (3,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Importancementioning
confidence: 99%
“…The mechanisms involved include altering the biophysical properties or cholesterol content of the cellular membranes in which they are found (Amini-Bavil-Olyaee et al, 2013;Li et al, 2013;Desai et al, 2014). These proteins inhibit many enveloped viruses, including influenza A virus (IAV), the flaviviruses WNV and DENV, severe acute respiratory syndrome coronavirus, hepatitis C virus, and Ebola virus (Brass et al, 2009;Zhu et al, 2015;Gorman et al, 2016) as well as HIV-1 and SIV (Lu et al, 2011). We and others identified new antiviral functions of IFITM proteins during HIV-1 infection: IFITM3 in the virus-producing cell is incorporated into nascent virions and decreases virus-cell fusion (Compton et al, 2014;Tartour et al, 2014;Yu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%